An Overview of Education and Training of Medical Informatics in India - Sarbadhikari, S. N.; Gogia, S. B. (Yearbook of Medical Informatics, 2010)
Background: Medical Informatics in India is still in its infancy. Although the Indian Association for Medical Informatics (IAMI) was foundedin1993, proposed bymajorhealthcaredelivery institutions, the absence of independent career options in medical informatics in India hasresulted eitherinthe exodusofthe needed facultymembersfor supporting education in the field. However, this situation may have been changing in the past few years, but a large gap exists which needs to be filled up quickly. The purpose of this report is to provide an assessment of the present situation of research and training in medical informatics in India, and its implications for future development of the field.Objectives: To assess the current situation regardingthe opportunities for research and education in Medical Informatics in India and related issues like availability of career options.Methods: Asurveyquestionnairewassentbypostalmailtowell-known Indian institutions engaged in medical informatics training and research. In addition, key stakeholders working towards impartingeducation and awareness on the principles and practice of medical informatics were contacted to provide information about training and researchinmedicalinformaticsinIndia.This was a purposivesamplingbased onpriorknowledge. Theresponseswerethematicallyanalyzed.Results: A total of six courses were identified in the survey. These were administered through face to face (F2F), e-learningand other modes of distance learning. In general, most of the students are graduates in medicine (allopathic, homeopathic, ayurvedic), allied sciences (nursing, physiotherapy) and medical administrators or graduates in engineering or library and information sciences. Most of them are also working, thus, the majority of the courses are for part-timers and act as on-job value addition. Most of the courses however do not directly train for jobs. Therefore, as most of the participants are already working somewhere, the question of placement due to the course may not be measurabledirectly. Since most of the students from India are already employed, by attending this course they gain further insights into health informaticsthat they want to pursue as a career.
Keywords: e-learning; Medical Informatics training; India